Epigenetic insights into an epimutant colorless non-ripening: from fruit ripening to stress responses - Zhu, Huihui; Yang, Jian Li; Chen, Weiwei (Frontiers in Plant Science, 2024)
The epigenetic machinery has received extensive attention due to its involvement in plant growth, development, and adaptation to environmental changes. Recent studies often highlight the epigenetic regulatory network by discussing various epigenetic mutants across various plant species. However, a systemic understanding of essential epigenetic regulatory mechanisms remains limited due to a lack of representative mutants involved in multiple biological processes. Colorless Non-ripening (Cnr), a spontaneous epimutant isolated from a commercial population, was initially characterized for its role in fruit ripening regulation. Cnr fruits exhibit an immature phenotype with yellow skin, attributed to hypermethylation of the SQUAMOSA PROMOTER BINDING PROTEIN-LIKE-CNR (SlSPL-CNR) promoter, resulting in the repression of gene expression. In addition to DNA methylation, this process also involves histone modification and microRNA, integrating multiple epigenetic regulatory factors. Interestingly, knockout mutants of SlSPL-CNR display phenotypical distinctions from Cnr in fruit ripening, indicating complex genetic and epigenetic control over the non-ripening phenotype in Cnr fruits. Accumulating evidence suggests that Cnr epimutation is pleiotropic, participating in various biological